PENGUATAN PENDIDIKAN AGAMA ISLAM MELALUI HAFALAN FURUDHUL AINIYAH DI SMP NURUL JADID PAITON - Sulistiawati Sulistiawati (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2017)
This research is intended to search and information about the strengthening of Islamic religious education (PAI) through the recitation of furudhul Ainiyah which is carried out in Nurul Jadid Paiton Junior High School. The method of this research is by qualitative method with case study method, to express. That is more intense and deep with the above phenomenon. Technique of completion of data and information is done through interview, observation, study study, and literature study. The findings of this research are 1). Students or students are required to complete the recitation of Furudhul Ainiyah as a condition to take the odd semester and even semester exam and become a requirement for class and graduation increase. 2). the implementation of the furudhul Ainiyah memorization is performed on Thursday and Friday nights and Tuesday nights, and can also be done during normal day breaks, 3). The responsible and recipient of the rote deposit are PAI teachers and their homeroom teachers, 4). For students and students who can not read written Al-qur'an is not subject to rote burden, but get special coaching related to Al-Qur'an reading written by the religious coordinator of students. 5). Memory materials include Aqidah, Fiqih or Amaliyah materials, and daily prayers for students of VII and VIII semerter 1 and 2, while for classes IX semesters 1 and 2 cover the material of the Qur'an and Fiqh. 6). (a). Principal, (b). Vice Principal of the curriculum section, (c). Coordinator of students' religious activities, (d). Teacher / teacher of PAI, (e). Homeroom, (e). Student religious coordinator, (f). Student.